The Mycobacterial Membrane: A Novel Target Space for Anti-tubercular Drugs - Chen, Huan; Nyantakyi, Samuel A.; Li, Ming; Gopal, Pooja; Aziz, Dinah B.; Yang, Tianming; Moreira, Wilfried; Gengenbacher, Martin; Dick, Thomas; Go, Mei L. (Frontiers in Microbiology, 2018)
Tuberculosis (TB) poses an enduring threat to global health. Consistently ranked among the top ten causes of death worldwide since 2000, TB has now exceeded HIV-AIDS in terms of deaths inflicted by a single infectious agent. In spite of recently declining TB incident rates, these decreases have been incremental and fall short of threshold levels required to end the global TB epidemic. As in other infectious diseases, the emergence of resistant organisms poses a major impediment to effective TB control. Resistance in mycobacteria may evolve from genetic mutations in target genes which are transmitted during cell multiplication from mother cells to their progeny. A more insidious form of resistance involves sub-populations of non-growing (‘dormant’) mycobacterial persisters. Quiescent and genetically identical to their susceptible counterparts, persisters exhibit non-inheritable drug tolerance. Their prevalence account for the protracted treatment period that is required for the treatment of TB. In order to improve the efficacy of treatment against mycobacterial persisters and drug-resistant organisms, novel antitubercular agents are urgently required. Selective targeting of bacterial membranes has been proposed as a viable therapeutic strategy against infectious diseases. The underpinning rationale is that a functionally intact cell membrane is vital for both replicating and dormant bacteria. Perturbing the membrane would thus disrupt a multitude of embedded targets with lethal pleiotropic consequences, besides limiting the emergence of resistant strains. There is growing interest in exploring small molecules as selective disruptors of the mycobacterial membrane. In this review, we examined the recent literature on different chemotypes with membrane perturbing properties, the mechanisms by which they induce membrane disruption and their potential as anti-TB agents. Cationic amphiphilicity is a signature motif that is required of membrane targeting agents but adherence to this broad physical requirement does not necessarily translate to conformity in terms of biological outcomes. Nor does it ensure selective targeting of mycobacterial membranes. These are unresolved issues that require further investigation.